1996
DOI: 10.1093/oxfordjournals.ndt.a027263
|View full text |Cite
|
Sign up to set email alerts
|

Frequent involvement of the internal cuff segment in CAPD peritonitis and exit-site infection--an ultrasound study

Abstract: We conclude that peritonitis and exit-site infections are frequently accompanied by involvement of the catheter tract. The localization of infection to the internal cuff region in cases of exit-site infection probably occurred as a result of downward migration along the catheter tract. This supports the notion that ideally the exit site should be pointing caudally or that the peritoneal catheter have a swan-neck configuration. With regard to peritonitis, infection within the peritoneal cavity appears to extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 3 publications
1
25
0
1
Order By: Relevance
“…Some patients with clinical features of ESI alone actually have occult infection of the catheter tunnel and internal cuff, which may be revealed by sonography (15,(176)(177)(178), and the presence of occult tunnel involvement predicts subsequent catheter loss (177). Possible indications for ultrasonographic examination of catheter tunnel are summarized in Table 3.…”
Section: Clinical Presentation and Assessmentmentioning
confidence: 99%
“…Some patients with clinical features of ESI alone actually have occult infection of the catheter tunnel and internal cuff, which may be revealed by sonography (15,(176)(177)(178), and the presence of occult tunnel involvement predicts subsequent catheter loss (177). Possible indications for ultrasonographic examination of catheter tunnel are summarized in Table 3.…”
Section: Clinical Presentation and Assessmentmentioning
confidence: 99%
“…Tunnel involvement was detected by US in seven (53.8%) of the 13 patients with peritonitis, in four of five S. aureus induced peritonitis, in one of two S. epidermidis peritonitis and in one of three gram negative peritonitis and two of three peritonitis without any grown. In the study reported by Korzets et al [13] in peritonitis the findings were mainly localized to the internal cuff region. Our findings were in agreement with those of Korzets et al [13].…”
Section: Discussionmentioning
confidence: 83%
“…In the study reported by Korzets et al [13] in peritonitis the findings were mainly localized to the internal cuff region. Our findings were in agreement with those of Korzets et al [13].…”
Section: Discussionmentioning
confidence: 83%
“…Using clinical criteria, rates of tunnel infection (primarily S. aureus) are 0.12/year, while with the use of sonography, rates climb to 0.35/ year. At least 50% of S. aureus exit-site infections are associated with tunnel infections [57][58][59][60].…”
Section: Diagnosis and Management Of Exit-site And Tunnel Infectionsmentioning
confidence: 99%